MSMES MARKET EXPANSION STRATEGY: SYNERGY OF HALAL CERTIFICATION AND DIGITAL MARKETING - Jailani, Novalini; Andrean, Rizky; Anwar, Khairul; Gunawan, Muhammad Ali (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
This study explores the strategic approach of combining Halal certification and digital marketing to enhance market expansion for Micro, Small, and Medium Enterprises (MSMEs). This study investigates how the synergy between Halal certification and digital marketing can be a dual strategy to penetrate new markets and increase sales volume. This research uses a descriptive qualitative approach with a type of library research. The data used in this study came from books, journal articles, and reports relevant to the research topic. The findings reveal that Halal certification significantly increases consumer confidence and market access. When paired with digital marketing, MSMEs experience substantial growth in both market reach and customer base. This study contributes to the growing body of literature on MSME growth strategies, demonstrating that the integration of Halal certification and digital marketing can serve as a powerful tool for market expansion, especially in culturally and religiously diverse markets. The synergy of Halal certification and digital marketing presents a viable strategy for MSMEs looking to expand their market presence in both local and international contexts. Abstrak Penelitian ini mengeksplorasi pendekatan strategis penggabungan sertifikasi Halal dan pemasaran digital untuk meningkatkan perluasan pasar bagi Usaha Mikro, Kecil, dan Menengah (UMKM). Studi ini menyelidiki bagaimana sinergi antara sertifikasi Halal dan pemasaran digital dapat berfungsi sebagai strategi ganda untuk menembus pasar baru dan meningkatkan volume penjualan. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan jenis penelitian kepustakaan. Data yang digunakan dalam penelitian ini berasal dari buku, artikel jurnal dan laporan yang relevan dengan topik penelitian. Temuan mengungkapkan bahwa sertifikasi Halal secara signifikan meningkatkan kepercayaan konsumen dan akses pasar. Ketika dipasangkan dengan pemasaran digital, UMKM mengalami pertumbuhan substansial baik dalam jangkauan pasar maupun basis pelanggan. Studi ini berkontribusi pada semakin banyak literatur tentang strategi pertumbuhan UMKM, menunjukkan bahwa integrasi sertifikasi Halal dan pemasaran digital dapat berfungsi sebagai alat yang ampuh untuk ekspansi pasar, terutama di pasar yang beragam secara budaya dan agama. Sinergi sertifikasi Halal dan pemasaran digital menghadirkan strategi yang layak bagi UMKM yang ingin memperluas kehadiran pasar mereka baik dalam konteks lokal maupun internasional.